STRUCTURE AND TRENDS OF THE INSURANCE SECTOR IN ROMANIA - MIRELA MONEA (Annals of the University of Petrosani: Economics, 2015)
The aim of the paper is to present the structure of the insurance sector from Romanian economy and the main trends in this sector in last years, based on the most important aspects such as share of foreign capital in this sector, gross written premiums, and indemnity payments, both from life and general insurance, density and penetration degree of the insurance activity, the results registered by the insurance companies